DEMENTIA SCREENING IN OLDER PEOPLE IN TANGERANG - Renata Komalasari; Desy Sihite (Universitas Pelita Harapan, 2019)
Early recognition of dementia syndrome can result in earlier intervention, thus earlier prevention and better management of dementia. However, there is a difficulty with instruments to screen for dementia in developing country. Low education, illiteracy and innumeracy of the ageing population may be screened positive for dementia. The Rowland Universal Dementia Screening Assessment Scale (RUDAS) was developed for cognitive function measurement for multi-cultural population with strong reliability and validity and had been validated in countries across the world. However, the literatures had reported no dementia screening studies with the use of the RUDAS in the Indonesian community. This study was the first study to screen for dementia utilising the Rowland Universal Dementia Assessment in the Indonesian community, which was undertaken in 2016 in Bencongan Indah, a subdistrict of a city in Banten. This was a descriptive study to screen for dementia using the RUDAS in the Indonesian community. Data was collected using purposive sampling with inclusion criteria: adults age 60 and over, Indonesian-speaking participants, there was no apparent acute illness that could affect the performance of the test. The validity and reliability of the RUDAS were assessed prior to the main study on 35 participants who had similar characteristics with the study respondents. The Indonesian version of the RUDAS instrument was assessed for validity and reliability prior to the main study. This study showed that out of 60 elderly respondents of 60-74 years old in the study, half (50%) had mild to moderate cognitive impairment, as scored 22-26 on the RUDAS. However, the study lacked investigation of demographic factors affecting the RUDAS performance. Recommendations Further study validating the use of the Indonesian version of the RUDAS is warranted.